Walking as soft mobility: A multi-criteria GIS-based approach for prioritizing tourist routes - Ghazal Hassanshahi; Ali Soltani; Maryam Roosta; Sajad Askari (Frontiers of Architectural Research, 2023)
Walking, as the main mode of soft mobility, has become an integral aspect of urban tourism. The development of pedestrian tourist routes plays a crucial role in enhancing the positive walking experience in urban tourist destinations. This research employs a hybrid multi-criteria decision-making (MCDM) with GIS to rank street segments, establishing walking-oriented tourist paths in Shiraz's historic district, Iran. The initial steps involve identifying pivotal criteria through literature reviews and expert surveys. The Analytical Hierarchy Process (AHP) establishes criteria and sub-criteria weights using input from 30 experts. The Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) then prioritizes street segments based on sub-criteria such as traffic safety, image ability and heritage assets, security, land use and activity, accessibility, comfort and convenience, and human scale. Furthermore, a Space Syntax analysis (SSA) is conducted to evaluate the morphology of the street network in the study area and identify streets with potential for pedestrian movement. By integrating these analyses, a prime corridor for a pedestrian tourist route is identified. This study offers planners and policymakers a valuable tool for pre-investment decision-making, aiding the promotion of walkability in tourist-centric areas.